Determining the Impacts of Stone Quarry Works On Riparian Vegetation of River Molo in Rongai Sub County, Nakuru County, Kenya - Kipyator Dennis; Michura Eliud Garry; Koskei Edna (Kabarak University, 2025)
Abstract The contribution made by stone quarrying to the Gross Domestic Product (GDP) in many countries globally is enormous. Whether small or large stone quarrying is inherently disruptive and can cause detrimental effects on the fragile riparian vegetation. This research determining the status of riparian vegetation between 2000 Molo and establishing the effects of stone quarry works on riparian vege tation. A descriptive survey design was adopted where 404 household were randomly sampled from a total of 35,545 households in Visoi, Soin and Mosop wards. 15 key informants were purposively sampled uestionnaires, interview schedules and Geographical Information System (GIS) and Remote sensing (RS) instruments were The obtained data was analyzed using SPSS (Version remote sensing (time series) to analyze changes in riparian vegetation using the Normalized Difference Vegetation Index (NDVI). The findings revealed a significant decline in riparian vegetation attributed to land use changes driven by poor agricultural practices and quarrying purposively selected quarries were found to be located meters away from the river, where one was abandoned with no sign of reclamation, thus directly affecting the health and integrity of the riparian vegetation. It was also noted that massive heaping of quarry overburden and deep excavation accelerated felling of regeneration and increased soil erosion. These findings will be useful to inform the best quarrying practices to reduce detrimental impacts on riparian vegetation and a foundation for policy development sector at county and national level.
Full text
Keywords: Geographical Information System; Normalized Difference Vegetation Index; Riparian Vegetation; Quarrying